Use of intravenous cyclizine in cardiac chest pain. Issue 1 (22nd December 2005) - May, Gabby; Kumar, Ricky
Abstract : A short cut review was carried out to establish whether cyclizine adversely affected haemodynamic parameters in patients with cardiac disease. A total of 70 papers were found of which one presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results, and study weaknesses of this best paper are tabulated. The clinical bottom line is that cyclizine should be avoided in patients with acute coronary events.